Adhesive composition, preparation method of adhesive composition, structural adhesive and application of structural adhesive

By using an adhesive composition containing magnetic nanoparticles and expandable particles in CTP technology, the problem of difficulty in disassembling of the adhesive is solved, and the rapid and safe disassembly of the battery pack and resource recycling are achieved, which meets environmental protection requirements.

CN119752382AActive Publication Date: 2025-04-04BYD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411377891.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-04-04
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

Adhesive connections in CTP technology are difficult to disassemble during the repair and recycling of battery packs, resulting in high costs and waste of resources, and existing degreasers are inefficient and unfriendly.

Method used

Adhesive compositions including adhesive resin, MnxZn1-xFe2O4 magnetic nanoparticles and expandable particles are used to trigger expansion of expandable particles under an alternating magnetic field, reducing the strength of the adhesive and facilitating disassembly.

Benefits of technology

It realizes rapid and non-destructive disassembly of adhesives, improves the disassembly efficiency and safety of battery packs, meets green and environmental protection requirements, and helps efficient resource recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to an adhesive composition and a preparation method thereof, a structural adhesive and application of the structural adhesive, the adhesive composition comprises adhesive resin, magnetic nano-particles and expandable particles, the magnetic nano-particles are MnxZn1-xFe2O4, x is 0.6-0.9, and the expandable particles are magnetic nano-particles and MnxZn1-xFe2O4 and MnxZn1-xFe2O4 and MnxZn1-xFe2O4 and MnxZn1-xFe2O4 and MnxZn1-xFe2O4. Based on 100 parts by weight of the adhesive composition, the content of the adhesive resin is 60-95 parts by weight, the content of the magnetic nanoparticles is 2-30 parts by weight, and the content of the expandable particles is 2-30 parts by weight. The adhesive composition disclosed by the invention can rapidly emit heat under the action of an alternating current magnetic field, so that the efficiency and the safety of an adhesive in a dismounting process are effectively improved, and the requirements of environmental protection are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition and a preparation method thereof, a structural adhesive and applications thereof. Background Art

[0002] Currently, most new energy power battery PACKs use CTP (Cell to Pack) technology instead of mechanical assembly solutions, which can save or reduce intermediate modules, thereby improving PACK energy density, reducing PACK costs, and reducing assembly processes. However, the CTP structure requires a large amount of adhesives to connect and fix the battery cells. In order to ensure the safety and reliability of the entire vehicle during use, the adhesive must have sufficient strength, but this also causes great trouble for subsequent battery pack maintenance and recycling.

[0003] Power battery packs using CTP technology can only be replaced and cannot be repaired, and the cost of replacing the entire pack is very high. On the other hand, existing packs can only be disassembled by force, which greatly consumes manpower and material resources and poses potential safety risks. The disassembled battery cells are generally scrapped, which does not fully utilize resources.

[0004] Currently, an alternative to violent disassembly is to use a debonding agent, such as using a reducing solution to remove the bonding relationship between adjacent structural parts. The battery pack usually needs to be soaked in the debonding agent for several days to complete the debonding. This is inefficient and easily produces pollutants, which is very unfriendly to the environment. Summary of the invention

[0005] The purpose of the present disclosure is to provide an efficient and environmentally friendly adhesive composition and a preparation method thereof, a structural adhesive and applications thereof.

[0006] In order to achieve the above object, the present disclosure provides, in a first aspect, an adhesive composition, comprising an adhesive resin, magnetic nanoparticles and expandable particles, wherein the magnetic nanoparticles are Mn x Zn 1-x Fe2O4, x is 0.6-0.9; based on 100 parts by weight of the adhesive composition, the content of the adhesive resin is 60-95 parts by weight, the content of the magnetic nanoparticles is 2-30 parts by weight, and the content of the expandable particles is 2-30 parts by weight.

[0007] Optionally, based on 100 parts by weight of the adhesive composition, the content of the resin is 70-90 parts by weight, the content of the magnetic nanoparticles is 5-15 parts by weight, and the content of the expandable microparticles is 5-15 parts by weight.

[0008] Optionally, the magnetic nanoparticles are Mn 0.7 Zn 0.3Fe2O4 and / or Mn 0.8 Zn 0.2 Fe2O4.

[0009] Optionally, the particle size of the magnetic nanoparticles is 10-100 nm; and / or the particle size of the expandable particles is 10-60 μm.

[0010] Optionally, the magnetic nanoparticles include first magnetic nanoparticles with a particle size of 10-30 nm and second magnetic nanoparticles with a particle size of 30-50 nm, and a weight ratio of the first magnetic nanoparticles to the second magnetic nanoparticles is 1:(0.5-2); and / or, The expandable particles include first expandable particles with a particle size of 10-25 μm and second expandable particles with a particle size of 25-40 μm, and the weight ratio of the first expandable particles to the second expandable particles is 1:(0.5-2).

[0011] Optionally, the expandable particles are of a core-shell structure, wherein the inner core particle size of the expandable particles is 5-30 μm, and the outer shell thickness of the expandable particles is 5-30 μm.

[0012] Optionally, the shell material of the expandable particles includes at least one of polyacrylonitrile-methyl acrylate copolymer, polyacrylonitrile-methyl methacrylate copolymer, polyvinylidene chloride-methyl acrylate copolymer and polyvinylidene chloride-methyl methacrylate copolymer; and / or, The core material of the expandable particles includes at least one of C1-C6 alkanes, C2-C6 alkenes and C2-C6 alkynes.

[0013] Optionally, the adhesive resin includes at least one of polyurethane resin, epoxy resin, acrylic resin and silicone resin.

[0014] In a second aspect of the present disclosure, a method for preparing the adhesive composition according to the first aspect of the present disclosure is provided, the method comprising: mixing an adhesive resin, magnetic nanoparticles and expandable microparticles to obtain an adhesive composition; The mixing conditions include: temperature of 40-60°C, vacuum degree of 10 -5 ~10Pa, time is 1~6 h.

[0015] A third aspect of the present disclosure provides a structural adhesive comprising the adhesive composition described in the first aspect of the present disclosure and an optional curing agent.

[0016] A fourth aspect of the present disclosure provides an application of the structural adhesive described in the third aspect of the present disclosure in a new energy power battery pack.

[0017] Through the above technical scheme, the adhesive composition disclosed in the present invention includes an adhesive resin, magnetic nanoparticles and expandable microparticles. Under the condition of AC magnetic field, the expandable microparticles can be triggered to expand, reducing the strength of the adhesive, thereby meeting the demand for easy disassembly of the adhesive and facilitating resource recycling. By using special magnetic nanoparticles Mn x Zn 1- x Fe2O4, this material has excellent magnetic induction heating efficiency and can quickly generate heat under the action of an AC magnetic field, thereby effectively improving the efficiency and safety of the adhesive removal process and meeting green environmental protection requirements.

[0018] Other features and advantages of the present disclosure will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0019] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0020] In a first aspect, the present disclosure provides an adhesive composition, the adhesive composition comprising an adhesive resin, magnetic nanoparticles and expandable particles, wherein the magnetic nanoparticles are Mn x Zn 1-x Fe2O4, x is 0.6-0.9; based on 100 parts by weight of the adhesive composition, the content of the adhesive resin is 60-95 parts by weight, the content of the magnetic nanoparticles is 2-30 parts by weight, and the content of the expandable particles is 2-30 parts by weight.

[0021] The present disclosure provides an adhesive material that has the property of being easily disassembled under specific conditions by combining an adhesive resin, magnetic nanoparticles and expandable microparticles. The magnetic nanoparticles can generate heat to heat the composition in situ under the action of an alternating magnetic field, triggering the expandable microparticles to expand and reducing the strength of the adhesive, thereby meeting the demand for easy disassembly of the adhesive, facilitating resource recycling, and effectively improving the efficiency and safety of the adhesive disassembly process, meeting the requirements of green environmental protection. The composition is designed to meet the requirements for the disassembly of the adhesive connection structure, and is particularly suitable for occasions that require disassembly and recycling, such as the CTP (Cell to Pack) structure in the new energy power battery PACK, which can achieve rapid and non-destructive disassembly of the battery pack without the need for baking by large industrial equipment.

[0022] In a preferred embodiment, based on 100 parts by weight of the adhesive composition, the content of the adhesive resin is 70 to 90 parts by weight, the content of the magnetic nanoparticles is 5 to 15 parts by weight, and the content of the expandable microparticles is 5 to 15 parts by weight. When the above preferred component ratio is met, the disassembly efficiency is further improved.

[0023] According to the present disclosure, the magnetic nanoparticles are Mn x Zn 1-x Fe2O4, x is 0.6-0.9, this material has excellent magnetic heating efficiency, can quickly heat up under the action of an alternating magnetic field, and this thermal effect can be precisely controlled to ensure heating uniformity and efficiency. In a preferred embodiment, the magnetic nanoparticles are Mn 0.7 Zn 0.3 Fe2O4 and / or Mn 0.8 Zn 0.2 Fe2O4, the above materials have excellent magnetic induction heating efficiency, which is beneficial to further improve the disassembly efficiency.

[0024] Furthermore, the average particle size of the magnetic nanoparticles may be 10 to 100 nm, preferably 10 to 50 nm. In a preferred embodiment, the magnetic nanoparticles may include first magnetic nanoparticles with a particle size of 10 to 30 nm and second magnetic nanoparticles with a particle size of 30 to 50 nm, and the weight ratio of the first magnetic nanoparticles to the second magnetic nanoparticles may be 1:(0.5 to 2). In this way, the combination of two magnetic nanoparticles of different particle sizes is conducive to improving the dispersibility of the magnetic nanoparticles in the composition, and can generate heat more evenly and efficiently under the action of the AC magnetic field, thereby enhancing the overall magnetocaloric effect.

[0025] According to the present disclosure, the expandable particles can expand under the heating effect of magnetic nanoparticles, so that the adhesive undergoes overall structural expansion, and the strength and bonding force of the adhesive are significantly weakened, thereby making the structural parts easier to disassemble. The particle size of the expandable particles can be adjusted within a certain range. Specifically, the average particle size of the expandable particles can be 10~60 μm, preferably 10~40 μm. In a preferred embodiment, the expandable particles can include first expandable particles with a particle size of 10~25 μm and second expandable particles with a particle size of 25~40 μm. The weight ratio of the first expandable particles to the second expandable particles can be 1: (0.5~2). By combining expandable particles of different particle sizes, the thermal expansion effect under different AC magnetic field conditions can be achieved, thereby improving the disassembly efficiency.

[0026] In a specific embodiment, the expandable particles are a core-shell structure of volatile hydrocarbons encapsulated by thermoplastic resin. Preferably, the shell material of the expandable particles includes at least one of polyacrylonitrile-methyl acrylate copolymer, polyacrylonitrile-methyl methacrylate copolymer, polyvinylidene chloride-methyl acrylate copolymer and polyvinylidene chloride-methyl methacrylate copolymer; the core material of the expandable particles includes at least one of C1~C6 alkanes (such as n-pentane, hexane, etc.), C2~C6 olefins (such as ethylene, propylene, etc.) and C2~C6 alkynes (such as acetylene, propyne, etc.); the expandable particles obtained using the above materials have excellent expansion performance, which is beneficial to improving disassembly efficiency while reducing the impact on the environment.

[0027] Furthermore, by adjusting the core particle size and shell thickness of the expandable microparticles, the expansion ratio can be precisely controlled, further improving the disassembly efficiency. Specifically, the core particle size of the expandable microparticles can be 5-30 μm, and the shell thickness of the expandable microparticles can be 5-30 μm.

[0028] According to the present disclosure, the adhesive resin may include at least one of polyurethane resin, epoxy resin, acrylic resin and silicone resin, which have excellent comprehensive properties and are particularly suitable for scenes requiring high strength and durability such as automobiles. The weight average molecular weight of the resin can be adjusted within a wide range, specifically 50,000 to 1,000,000.

[0029] The adhesive composition disclosed in the present invention is particularly suitable for the CTP structure of new energy power battery PACK. By using this composition, on the one hand, it can ensure that the strength of the adhesive will not drop suddenly within the normal operating temperature range of the battery, meeting the reliability requirements. On the other hand, the battery PACK no longer requires mechanical force or chemical solvents when disassembling, but can be easily disassembled by applying an AC magnetic field at the appropriate position, which improves the disassembly efficiency and safety and meets the requirements of green environmental protection. Since the adhesive can be disassembled without damaging the connecting parts, the connecting parts can be recycled and reused more efficiently, which helps to improve resource utilization efficiency and promote green and sustainable development.

[0030] In a second aspect of the present disclosure, a method for preparing the adhesive composition of the first aspect of the present disclosure is provided, the method comprising: mixing an adhesive resin, magnetic nanoparticles and expandable particles to obtain an adhesive composition; wherein the mixing conditions include: a temperature of 40 to 60° C., a vacuum degree of 10 -5 ~10Pa, time is 1~6 h, the above conditions will not cause the expandable particles to expand, and at the same time are conducive to the uniform dispersion of the particles in the assembly.

[0031] In a preferred embodiment, the method further comprises pre-treating the magnetic nanoparticles before the mixing to prevent them from agglomerating in the adhesive composition. The pre-treatment may include placing the magnetic nanoparticles in deionized water and dissolving the agglomerates in a water bath; then adding oleic acid, stirring for a certain period of time under heating conditions, and finally washing with ethanol, and separating the magnetic nanoparticles with oleic acid coating with a permanent magnet.

[0032] A third aspect of the present disclosure provides a structural adhesive comprising the adhesive composition described in the first aspect of the present disclosure and an optional curing agent.

[0033] There is no particular limitation on the type of the curing agent, and the curing agent can be selected according to the type of the adhesive resin in the adhesive composition. For example, when a polyurethane resin is used as the adhesive resin, the curing agent can be selected from polyisocyanates. The amount of the curing agent can be adjusted within a certain range, specifically according to the type and amount of the adhesive resin. The weight ratio of the curing agent to the adhesive composition can be (1-6):1, preferably (2-4):1.

[0034] The structural adhesive disclosed in the present invention has the same beneficial effects as the adhesive composition described above, which will not be described in detail here.

[0035] A fourth aspect of the present disclosure provides an application of the structural adhesive described in the third aspect of the present disclosure in a new energy power battery pack.

[0036] Specifically, the new energy power battery pack has the structural adhesive, and the application may include: disassembling the new energy power battery pack under the action of an alternating magnetic field, wherein the intensity of the alternating magnetic field may be 60-200oe.

[0037] The present disclosure is further described in detail below through examples.

[0038] Example 1 The weight percentages of the components in the adhesive composition of this embodiment are as follows: 85wt.% polyurethane resin (weight average molecular weight is 100000), 10wt.% Mn 0.7 Zn 0.3 Fe2O4 magnetic nanoparticles (average particle size is 20 nm), 5wt.% expandable particles (average particle size is 25μm); the shell material of the expandable particles is polyacrylonitrile-methyl acrylate copolymer, the shell thickness is 15μm, the core is acetylene gas, and the core particle size is 10μm.

[0039] The production process is as follows: polyurethane resin, magnetic nanoparticles and expandable particles are mixed, heated to 60°C, stirred for 1 h under a vacuum degree of 10 Pa, then cooled to room temperature and sealed for storage.

[0040] Example 2 An adhesive composition was prepared according to the method of Example 1, except that the components and their weight percentages were as follows: 70 wt.% epoxy resin (weight average molecular weight of 100,000), 15 wt.% Mn 0.7 Zn 0.3 Fe2O4 magnetic nanoparticles (average particle size of 10 nm), 15 wt.% expandable particles (average particle size of 10 μm); wherein the shell material of the expandable particles is polyvinylidene chloride-methyl acrylate copolymer, the shell thickness is 5 μm, the core is propyne gas, and the core particle size is 5 μm.

[0041] Example 3 An adhesive composition was prepared according to the method of Example 1, except that the components and their weight percentages were as follows: 90 wt.% acrylic resin (weight average molecular weight of 150,000), 5 wt.% Mn 0.7 Zn 0.3 Fe2O4 magnetic nanoparticles (average particle size of 50 nm), 5wt.% expandable particles (average particle size of 40 μm); the shell material of the expandable particles is polyacrylonitrile-methyl methacrylate copolymer, the shell thickness is 30 μm, the core is propylene gas, and the core particle size is 30 μm.

[0042] Example 4 The adhesive composition was prepared according to the method of Example 1, except that the magnetic nanoparticles were Mn 0.8 Zn 0.2 Fe2O4 (average particle size 20 nm).

[0043] Example 5 The adhesive composition was prepared according to the method of Example 1, except that the magnetic nanoparticles were Mn 0.6 Zn 0.4 Fe2O4 (average particle size 20 nm).

[0044] Example 6 An adhesive composition was prepared according to the method of Example 1, except that the magnetic nanoparticles included Mn with a particle size of 10-30 nm. 0.7 Zn 0.3 Fe2O4 and Mn with a particle size of 30~50 nm 0.7 Zn 0.3 Fe2O4, the weight ratio of the two is 1:1.

[0045] Example 7 An adhesive composition was prepared according to the method of Example 1, except that the expandable particles were first expandable particles with a particle size of 10-25 μm and second expandable particles with a particle size of 25-40 μm; wherein the shell materials of the first expandable particles and the second expandable particles were both polyacrylonitrile-methyl acrylate copolymer, and the cores were both acetylene gas; the shell thickness of the first expandable particles was 5-10 μm, and the core particle size was 5-15 μm; the shell thickness of the second expandable particles was 15-20 μm, and the core particle size was 10-20 μm.

[0046] Example 8 An adhesive composition was prepared according to the method of Example 1, except that the components and their weight percentages were as follows: 60 wt.% polyurethane resin, 20 wt.% Mn 0.7 Zn 0.3 Fe2O4 magnetic nanoparticles, 20wt.% expandable particles.

[0047] Example 9 An adhesive composition was prepared according to the method of Example 1, except that the components and their weight percentages were as follows: 95 wt.% polyurethane resin, 2 wt.% Mn 0.7 Zn 0.3 Fe2O4 magnetic nanoparticles, 3wt.% expandable particles.

[0048] Example 10 An adhesive composition was prepared according to the method of Example 1, except that Mn 0.7 Zn 0.3 The average particle size of Fe2O4 magnetic nanoparticles is 100 nm, and the average particle size of expandable particles is 60 μm.

[0049] Comparative Example 1 The adhesive composition was prepared according to the method of Example 1, except that the same amount of Mn 0.5 Zn 0.5 Fe2O4 (average particle size 20 nm) was used as magnetic nanoparticles to replace Mn 0.7 Zn 0.3 Fe2O4.

[0050] Comparative Example 2 The adhesive composition was prepared according to the method of Example 1, except that the same amount of nano-Fe3O4 (average particle size of 60 nm) was used as magnetic nanoparticles to replace Mn 0.7 Zn 0.3 Fe2O4.

[0051] Test Case The adhesive compositions of the embodiments and comparative examples are prepared as structural adhesives and subjected to performance tests. Specifically, the adhesive composition is fully mixed with a certain amount of an optional curing agent in a clean container. Use a blade to mark an area at one end of the wide side of the aluminum strip to define the overlap surface. Use a clean cleaning cloth dipped in 95% alcohol to wipe the overlap surface of the aluminum strip to remove impurities such as dust and oil on the overlap surface. The alcohol is cleaned and dried for more than 10 min. Apply the mixed glue on the overlap surface of the aluminum strip. After the glue is smoothed, quickly overlap and press, and then fix the two ends of the overlap surface with a clip. Pay attention to keep the two aluminum strips on the same horizontal line. The thickness of the glue layer is 0.2 mm, and the operation time is controlled to 20~40 min. After being fully cured, it is placed at room temperature for 7 days, and subsequent performance tests are carried out. The results are listed in Table 1.

[0052] Magnetic field heating temperature test method: Place it in a 120 oe AC magnetic field for 5 minutes, use an infrared thermometer to test the temperature of the structural adhesive, and record the results. Each group of samples is measured three times and the results are averaged.

[0053] Tensile shear test: GB / T 7124-2008 is used. After curing in a constant temperature and humidity chamber (25℃ / 50%RH) for more than 7 days, the test is performed. The sample is clamped on the fixture, and the distance from the clamp to the nearest bonding end is 50 mm±1mm. The tensile machine is stretched at a rate of 5 mm / min, and the curve is recorded. The maximum stress during the failure process is the failure load F (N), divided by the bonding area A (mm 2 ) to obtain the tensile shear strength δ (MPa): δ = F / A. The tensile shear strength at 25°C and magnetic heating temperature is tested in a temperature-controlled box. Each test requires at least three groups of samples and is tested in accordance with the requirements of the above tensile shear test; the sample to be tested is placed in a universal tensile testing machine with a temperature-controlled box for more than 30 minutes, and the test is performed after reaching a constant temperature. During the test, the door needs to be opened and closed for a certain period of time to keep the sample temperature constant, and the results are averaged. The difference in shear strength change is calculated according to the following formula: Δδ= shear strength at 25°C - shear strength at magnetic heating temperature Table 1

[0054] It can be seen from Table 1 that under the same AC magnetic field conditions, compared with the comparative example, the adhesive composition of the embodiment can reach a higher magnetic induction heating temperature, quickly reduce the shear strength of the structural adhesive, and has a high disassembly efficiency.

[0055] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0056] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0057] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. An adhesive composition, characterized in that: The adhesive composition comprises an adhesive resin, magnetic nanoparticles and expandable particles, wherein the magnetic nanoparticles are Mn x Zn 1-x Fe2O4, x is 0.6-0.9; based on 100 parts by weight of the adhesive composition, the content of the adhesive resin is 60-95 parts by weight, the content of the magnetic nanoparticles is 2-30 parts by weight, and the content of the expandable particles is 2-30 parts by weight.

2. The adhesive composition according to claim 1, wherein Based on 100 parts by weight of the adhesive composition, the content of the adhesive resin is 70 to 90 parts by weight, the content of the magnetic nanoparticles is 5 to 15 parts by weight, and the content of the expandable microparticles is 5 to 15 parts by weight.

3. The adhesive composition according to claim 1 or 2, wherein: The magnetic nanoparticles are Mn 0.7 Zn 0.3 Fe2O4 and / or Mn 0.8 Zn 0.2 Fe2O4.

4. The adhesive composition according to claim 1 or 2, wherein: The average particle size of the magnetic nanoparticles is 10-100 nm; and / or the average particle size of the expandable particles is 10-60 μm.

5. The adhesive composition according to claim 4, wherein: The magnetic nanoparticles include first magnetic nanoparticles with a particle size of 10-30 nm and second magnetic nanoparticles with a particle size of 30-50 nm, and the weight ratio of the first magnetic nanoparticles to the second magnetic nanoparticles is 1:(0.5-2); and / or, The expandable particles include first expandable particles with a particle size of 10-25 μm and second expandable particles with a particle size of 25-40 μm, and the weight ratio of the first expandable particles to the second expandable particles is 1:(0.5-2).

6. The adhesive composition according to claim 1 or 2, wherein: The expandable particles are of a core-shell structure, wherein the core particle size of the expandable particles is 5-30 μm, and the shell thickness of the expandable particles is 5-30 μm.

7. The adhesive composition according to claim 6, wherein: The shell material of the expandable particles includes at least one of polyacrylonitrile-methyl acrylate copolymer, polyacrylonitrile-methyl methacrylate copolymer, polyvinylidene chloride-methyl acrylate copolymer and polyvinylidene chloride-methyl methacrylate copolymer; and / or, The core material of the expandable particles includes at least one of C1-C6 alkanes, C2-C6 alkenes and C2-C6 alkynes.

8. The adhesive composition according to claim 1 or 2, wherein: The adhesive resin includes at least one of polyurethane resin, epoxy resin, acrylic resin and silicone resin.

9. A method for preparing the adhesive composition according to any one of claims 1 to 8, characterized in that: The method comprises: mixing an adhesive resin, magnetic nanoparticles and expandable microparticles to obtain an adhesive composition; The mixing conditions include: temperature of 40-60°C, vacuum degree of 10 -5 ~10Pa, time is 1~6 h.

10. A structural adhesive, characterized in that: The invention comprises the adhesive composition according to any one of claims 1 to 8 and an optional curing agent.

11. Application of the structural adhesive according to claim 10 in new energy power battery packs.

Citation Information

Patent Citations

  • Preparation method of magneto-thermal stickiness-reducing adhesive tape

    CN110669453A

  • Protective colloid and use method thereof

    CN113046010A

  • Induction heat curing adhesive

    CN116057145A

  • Process for adhesive separation of bonded joints

    US20050039848A1